SENTRA USAHA KECIL MENENGAH DENGAN PENDEKATAN ARSITEKTUR NEO VERNAKULAR DI SURAKARTA - Eva Anggraini; Widi Suroto; Tri Joko Daryanto (ARSITEKTURA, 2016)
The existence of UKM (Small and Medium Enterprises) Center in Surakarta motivated by the high potential of UKM in Surakarta and the lack of facilities for the center of UKM in Surakarta. The purpose of the final research is to get the plan and design concept of UKM Center in Surakarta that were able to accommodate trading activities, human resource developing, and promoting UKM product, using Neo Vernacular Architecture as design approach. The problem that arises is how to translate the characteristic of Neo Vernacular into the design of UKM Center. The method used is qualitative descriptive graphical which is decomposition of data and information with picture/visual illustration as media based on existing normative theory. In this research, studies are done to obtain the application of the characteristic of Neo Vernacular Architecture for UKM Center in Surakarta. The result is a design concept of UKM facility, which serves as a means of trading, developing and promoting in the form of building area by applying the characteristic of Neo Vernacular in the appearance of the building so as to create the atmosphere that is present but do not leave the local character.